2020
DOI: 10.1002/fsn3.1388
|View full text |Cite
|
Sign up to set email alerts
|

Role of phospholipase C in banana in response to anthracnose infection

Abstract: Phospholipase C (PLC) plays an important role in plant immunity, and anthracnose caused by the Colletotrichum species is a common postharvest disease of the banana fruit. This study aims to evaluate the role of PLC in anthrax resistance in banana. The experimental group of banana samples was treated with a banana anthracnose conidia suspension, and the control group was treated with distilled water. After inoculation, the groups were sprayed with ethephon, and indicators, such as hardness and conductivity chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Citrus sinensis PI‐PLC genes respond to the early infection process by Penicillium digitatum , which can be promoted by abscisic acid (Lafuente et al, 2021 ). The PI‐PLC gene in banana ( Musa acuminata ) responds to infection by Colletotrichum musae , impacting conductivity and the DAG system (Table 2 ) (Shuai et al, 2020 ). PLC activity was decreased by BTH and SA in apples infected by Penicillium expansum and longan infected by Phomopsis longanae , respectively, thereby reducing postharvest diseases in fruit (Chen et al, 2020 ; Gong et al, 2021 ).…”
Section: Plcs In Plant Disease Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Citrus sinensis PI‐PLC genes respond to the early infection process by Penicillium digitatum , which can be promoted by abscisic acid (Lafuente et al, 2021 ). The PI‐PLC gene in banana ( Musa acuminata ) responds to infection by Colletotrichum musae , impacting conductivity and the DAG system (Table 2 ) (Shuai et al, 2020 ). PLC activity was decreased by BTH and SA in apples infected by Penicillium expansum and longan infected by Phomopsis longanae , respectively, thereby reducing postharvest diseases in fruit (Chen et al, 2020 ; Gong et al, 2021 ).…”
Section: Plcs In Plant Disease Resistancementioning
confidence: 99%
“…Pathogen infection induces host membrane hydrolysis, which affects the abundance and efficiency of the PLC enzyme and causes rapid phospholipid signal transduction, thereby promoting plant disease resistance (Abd‐El‐Haliem et al, 2017 ). However, studies have shown that PLC genes are up‐regulated in some infected plants and down‐regulated in others, and the functional differentiation associated with down‐regulated PLC genes remains unknown (Pokotylo et al, 2013 ; Shuai et al, 2020 ), therefore evaluating changes in PLC gene expression and enzyme activity during plant–pathogen interactions is highly meaningful. Although it is known that plants contain both PI‐PLC and NPC molecules that mediate phospholipid hydrolysis and DAG production, it is unclear which of these enzymes plays the primary role in disease resistance (Hong et al, 2016 ), therefore the function of PLC should be determined using gene editing technology to explore PLC activity during plant disease resistance.…”
Section: Plcs In Plant Disease Resistancementioning
confidence: 99%
“…C. musae performs two types of infections namely, latent (quiescent) and wound (Ciofini et al, 2022; Prusky et al, 2000). Fruit damage in export banana is mainly caused by wound anthracnose (Chillet et al, 2007), and latent infection of banana fruits starts when the crop is in the plantations and develops symptoms on the peel at the stage of fruit ripening (Chillet et al, 2007; Shuai et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…crop is in the plantations and develops symptoms on the peel at the stage of fruit ripening (Chillet et al, 2007;Shuai et al, 2020).…”
mentioning
confidence: 99%